Studi Komparasi Karakter Bentuk Estetik Desain Pesawat Tempur F-16 dan SU-27 - Larasmoyo Nugroho (Journal of Visual Art and Design, 2008)
Defense and security are serious business, as they represent the integrity and dignity of a nation. It is understandable to assess military power and facilities as crucial to a nation's defense, shown in the use of fighter airplanes. A fighter airplane serves as a window to represent nation's values, philosophy and ideology; appeared through its design form and defense ability. The presented paper explores and compares 2 (two) types of fighter airplane, F-16 of US and SU-27 of Russia, in order to observe and characterize their design forms. Having acknowledged the characteristic of their design forms as tangible aspect of analysis, it is identified that this characteristic can be split into form design and numerical design. Comparative assessment of both fighter airplanes indicates that F-16 fighter airplane of US appears smaller than the SU-27 of Russia. The smaller size of F-16 form was meant to have superior maneuver-ability for air-to-air combat, while the size of SU-27 was meant to accommodate multi-tasking aspects of fighter airplane (air-to-air combat and interceptive act). As results, both airplane forms express different views and ideological perspectives. The F-16 of US shows great and superior ability to carry special task of becoming combat airplane (thrive to perfection), coming with a hefty price and catered for great quality.  On the other hand, SU-27 of Russia shows a wider purpose and not necessarily has superior ability in order to carry diverse tasks of an airplane (multi-tasking), coming with a cheaper price and catered in a great quantity.  Thus, it can be deduced that the American designer of fighter airplane tends to acknowledge specialization of military purpose compare to the Russian's generalization of military purpose.